Student Teachers' Perceptions of Bullying in Schools - Gumuseli, Ali Ilke; Hacifazlioglu, Ozge; Cakmak, Esra (KAMLA-RAJ ENTERPRISES, 2014)
The purpose of the study is to investigate and provide insights into the problems concerning school bullying. The objective of the research was to investigate the following issues like What kinds of behaviors are defined as bullying by student teachers?, How frequently do students engage in bullying behaviors?, Where do these behaviors most commonly take place in a typical school environment?, and How do student teachers deal with incidents of bullying? The present study applies a quantitative research design. To formulate availability sampling, student teachers were selected from the teaching certificate program in Yildiz Technical University. A total of 400 student teachers participated in the study. The study explored that verbal bullying appeared the Most often perceived by the student teachers followed by emotional bullying as compared to physical bullying, and finally sexual bullying, was the least observed type of bullying.
Keywords: Bullying; Teachers; Schools; Perceptions; Education; EDUCATORS; CLIMATE; SAFETY; EXTENT; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics